THE MANAGERIAL USE OF DATA OBTAINABLE IN CONJUNCTION WITH LIFO. - Gordon, Myron J. (The Accounting Review, 1956)
The author of this article reviews the thesis that the last-in-first-out (LIFO) method of inventory valuation and an accounting system designed to provide management with internal data for control and decision compliment each other. He elaborates the LIFO theory, illustrating it with quotations. He then enumerates with examples, the data required by a manufacturing enterprise with a heterogeneous inventory under any variant to find its LIFO inventory and cost of goods sold. He considers the problems faced by a first-in-first-out (FIFO) firm while demonstrating that periodic reports derived from a standard cost system compliments LIFO, whereas they conflict with FIFO. He examines the question of whether a firm should price on a FIFO or a current cost basis as prices are subject to frequent changes. He discusses the ability of the purchasing department to buy at the right prices as an important factor of the success of the firm and the conditions under which a firm can be said to be speculating on a commodity.